Evidence of Criminal Acts of Origin in The Prevention and Eradication of Money Laundering Law Under Presumption of Innocence Principle. - Arafat J., Fadli Yasser; Bahri, Muhammad Fadhlan Fadhil; Ichsan A.H., Muhammad Arfhani; Asrullah (Alauddin Law Development Journal, 2024)
This study aims to determine the contradiction between the provisions on the proof of the original criminal act with the principle of Presumption of Innocence in the Anti-Money Laundering Law 2010. The research was conducted with normative research method using statutory approach, conceptual approach, historical approach, and historical approach. Data analysis uses qualitative descriptive analysis with data analysis methods that are connected to existing principles, theories so that conclusions can be drawn on the answers and problems. The research results show that The provisions of the article have violated the principle of presumption of innocence in criminal law and also harmed human rights. The crime of money laundering is also a further criminal offense that has a prerequisite criminal offense so that without the initial criminal offense or the prerequisite criminal offense, the act can no longer be defined as a money laundering criminal offense.